Organisational climate, workplace bullying and employee health in selected service sectors of Pakistan / Mehwish Iftikhar - Mehwish , Iftikhar (2019)
Workplace bullying is a devastating problem which needs to be addressed given its adverse effects and implications. This study identified several gaps in the literature when expanded specifically to service sector of Pakistan where the problem of bullying is rife (Bashir & Malik, 2011; Naseer & Khan, 2015; Ahmad et al., 2017). There is a scarcity of academic research on the understanding of workplace bullying (traditional and cyberbullying). As an emerging field of research area, detailed understanding about the predictors of cyberbullying have not been fully established. Very few studies have been conducted on studying the bundled impacts of workplace bullying (traditional bullying and cyberbullying) at workplace of organizations. This study is endeavored to fill up the gaps by focusing on organizational climate as a cause of workplace bullying (on the basis of frustration aggression theory and social interaction approach), technology (social networking and ICT) in relation to cyberbullying, and bundled effects of both the traditional and cyber bullying on employee health by considering General Strain Theory. Emotional Intelligence as a coping strategy has also been proposed and tested in this study in order to reduce the negative health impacts of bullying. In this quantitative cross sectional research, data is gathered from 382 employees in 4 service sectors (banking, telecom, hoteling and education) of Pakistan, with a response rate of 78%. Analysis has been done through Structural Equation Modeling (SEM) by using smartPLS version 3.2. Using NAQ-21 and NAQ-R on the basis of the cut-off criteria for measuring bullying and cyberbullying prevalence, the results highlighted that 59%, 53%, 48% and 37% of the respondents were categorized as bullied traditionally and 49%, 41%, 40% and 18% were cyberbullied in banking, telecom and hoteling and education service sectors respectively. Overall, the traditional bullying experienced a 49% whilst the cyberbullying was at 47%. Multiple dimensions of organizational climate are found to be the predictors of workplace bullying, while technology (social networking and ICT’s) is significantly related to the prevalence of cyberbullying at workplace of service sector organizations. Workplace bullying (traditional and cyber) depicted negative consequences on employee's health in the form of psychological, physiological and emotional health. Organizational climate also significantly effects employee health directly. Results also highlighted the mediating effect of workplace bullying between the relationship of organizational climate and employee health (burnout and ill-health).Furthermore, Emotional Intelligence with its dimensions (self-awareness, self-regulation, motivation, empathy and social skills) moderates the relationship between workplace bullying and employee health (burnout and ill-health). This research gives new insights about various types of bullying (traditional and cyber) and its adverse effects and also contributes to the emergent dialogue of identifying the debilitating outcomes of both types of bullying. Organizations may use Emotional Intelligence as a coping strategy in order to reduce the negative effects of bullying by embedding it in the HR policy of the organization.